IMPLEMENTATION OF SCIENCE-BASED CREATIVE GAMES IN EARLY CHILDHOOD - Tutin Rahayu; Hamid Patilima (Adisam Publisher, 2025)
This study aims to analyze the implementation of creative science-based games in early childhood education at PAUD Cinta Kasih Ibu, Cengkareng Timur, West Jakarta. A qualitative approach with a case study method was used to explore the planning, implementation, and challenges of applying creative science-based games. Data were collected through participatory observation, in-depth interviews with teachers and school principals, and relevant documentation. The findings indicate that science-based games enhance critical thinking, exploration, and creativity in young children. However, implementation faces challenges such as limited facilities, insufficient teacher training, and varying levels of children's understanding of scientific concepts. This study recommends improving teacher training, developing more innovative learning media, and involving parents in strengthening children's scientific literacy from an early age.